Bauxite contamination in Kuantan effect on the property of the housing value - Nur Syamimi Syahraine, Abu Zaki (2017)
Nowadays, mining is important and a source of income especially for a country rich in mineral resources. Increasing demand from domestic and international industrial sectors has increased the production of mineral resources such as bauxite. The high market price and demand of bauxite in various sectors have been beneficial for Malaysia. However, in the pursuit of profit, a lot of negative factors such as environmental pollution and human’s health have affected the local community. Therefore, this issue should be taken seriously by the authorities to ensure that the community live in harmony and comfort. This research objective is to study the factors that can effects the housing prices, determine how the bauxite affects the property of the housing value and also examine the relationships exists between the bauxite and the property of the housing value. Based on a combination of literature review and questionnaire survey, this research explores contamination such as air pollution, water pollution and noise pollution that occurs during bauxite mining operations and the impacts of bauxite mining to human health and also the relationship between the bauxite and the property of the housing value. The research was conducted by provide and spread 50 sets of questionnaire survey to the respondents to obtain information about the impacts of environmental pollution, health problem occur and how far bauxite contamination effect the property of the housing value. Then, the total results of 50 complete sets of questions used for quantitative analysis. The results were analysed through SPSS methods using descriptive statistics and using average index methods. Most of the respondents give feedback that bauxite mining adverse impact on them. Dust pollution is the highest with 4.82, water pollution by 4.76 followed by 4.58 of average index of noise pollution. Many bad impacts also occur on the property of the housing value such as the dust deposited everywhere resulted the dirty house as well as decrease the aesthetics value of house. Therefore, residents agreed that bauxite contamination affects the value of residential property, especially people living near mining bauxite plant.